REPRESENTACIONES SOCIALES SOBRE “MUJER” EN MIEMBROS DE PAREJAS HETEROSEXUALES VIOLENTAS Y NO VIOLENTAS, SEGÚN ESTRATO SOCIOECONÓMICO, EDAD Y RELIGIÓN. (2016)
This article presents the description of the different social representations of "woman" on members of violent and non-violent heterosexual couples and their impact on the occurrence of episodes of violence against women in relationships. The sample consisted of 400 heterosexual subjects over 18 years, belonging to a ratio of violent or non-violent city of Barranquilla, Colombia, according to factors such as socioeconomic status, age, and religion. The results initially allowed to describe what are the social representations of women members of violent and non-violent heterosexual couples and establish that there is indeed a direct impact between social representations that are the subject of women and the appearance or not, cases of intimate partner violence against women, considering that according to what was observed in the groups of subjects pertaining to relations violent and nonviolent couples, such representations prevail upon her to act in relationships.